Effectiveness of dynamic neuromuscular stabilization exercises on clinical variables in postoperative rehabilitation of patients with lumbar disc herniation: a randomized controlled trial - Burak Buğday; Büşra Arısüt; Elif Esma Bayraktar; Ömer Şevgi̇n (BMC Musculoskeletal Disorders, 2026)
Abstract Purpose This study evaluates the effects of an 8-week Dynamic Neuromuscular Stabilization (DNS) program on disability, physical activity, and fear-avoidance behaviors in postoperative lumbar disc herniation (LDH) patients. Method The study was designed as a randomized controlled trial. Participants of both sexes, aged 35–50 years, were recruited from a single-center postoperative outpatient physiotherapy setting and randomized into DNS (intervention) and standard care (control) groups. The DNS program emphasized core stability, diaphragmatic breathing, and postural alignment. Outcomes were measured at baseline and after the 8-week intervention period using validated scales for disability (ODI), pain (VAS), physical activity (MET-minutes), and fear-avoidance (FDAQ). Data were analyzed using appropriate inferential statistical methods, with statistical significance set at p < 0.05. Results Baseline characteristics were comparable between groups ( p > 0.05). Post-intervention, a significant difference was observed between groups in physical activity level categories ( p = 0.001), with a shift toward higher activity levels in the intervention group. Physical activity (MET-min/week) was significantly higher in the intervention group at post-intervention ( p = 0.001). Post-intervention, the intervention group demonstrated significantly lower functional disability, pain at rest, pain during activity, and fear of daily activities compared to the control group (all p ≤ 0.001). Within-group analyses showed significant improvements in functional disability, pain, fear of daily activities, and physical activity in the intervention group (all p < 0.001). Conclusion DNS demonstrated superior efficacy compared to standard care, achieving clinically meaningful improvements across all metrics. These results highlight DNS as a promising approach for enhancing functional recovery and clinical outcomes in patients with LDH. Clinical trial number The protocol is registered with http://clinicaltrials.gov/15/August/2023 , Clinical Trial, NCT06005948).